Síntese e eficiência da quitosana catiônica no tratamento físico-químico da água - Bastiani, Vanessa Rossato de (2023)
Water intended for human consumption must meet the potability standards established by legal regulations. To ensure this, it is often necessary to carry out a series of treatment steps. These procedures typically involve the application of chemical agents, such as aluminum sulfate. However, the residual presence of these products in the water can lead to adverse impacts on the environment and human health. An alternative to address this issue is the adoption of cationic organic polymers as substitutes for conventional chemical agents. Chitosan, an organic polymer derived from chitin, plays a significant role in this context. However, under certain circumstances, modifications to the chitosan structure are required to enable its use as a cationic polysaccharide. One of the most commonly employed reagents for this purpose is 3-chloro-2-hydroxypropyltrimethylammonium chloride (CHPTAC). In this context, this research aimed to produce a cationic polysaccharide derived from chitosan through the cationization process in different aqueous media using the CHPTAC reagent. The final product was then applied in water treatment, with variations in dosages and pH. The treatment system was simulated using equipment known as the "Jar Test," followed by filtration with filter paper. The research revealed that the cationization of chitosan resulted in a degree of substitution of 1.39, 1.03, and 0.80, respectively, in QCSA, QCSB, and QCSN. The synthesized chitosans achieved removal efficiencies of up to 97.9% for turbidity and 97.2% for color. Unaltered chitosan (QP) achieved a removal percentage of 98.5% for turbidity and 99.1% for color. Among the evaluated dosages, those frequently mentioned with the highest removal percentages were 15 mg/L; however, higher dosages also demonstrated satisfactory results, especially for QP. Regarding the tested pH ranges, each flocculant analyzed exhibited better performance within a specific pH range, with acidic pH being the most frequent. The study demonstrated the effectiveness of chitosan, both in cationic and non-cationic forms, in the physicochemical water treatment process, playing a significant role in reducing color and turbidity. These results highlight that the use of organic flocculants is a viable alternative to replace widely employed inorganic coagulants.